Metamorphoses of memory of the the Russian-Serbian Brotherhood of War in Modern Serbia - A. Yu. Timofeev (Vestnik MGIMO-Universiteta)
The article considers the perception of World War II in modern Serbian society. Despite the stability of Serbian-Russian shared historical memory, the attitudes of both countries towards World wars differ. There is a huge contrast in the perception of the First and Second World War in Russian and Serbian societies. For the Serbs the events of World War II are obscured by the memories of the Civil War, which broke out in the country immediately after the occupation in 1941 and continued several years after 1945. Over 70% of Yugoslavs killed during the Second World War were slaughtered by the citizens of former Kingdom of Yugoslavia. The terror unleashed by Tito in the first postwar decade in 1944-1954 was proportionally bloodier than Stalin repressions in the postwar USSR. The number of emigrants from Yugoslavia after the establishment of the Tito's dictatorship was proportionally equal to the number of refugees from Russia after the Civil War (1,5-2% of prewar population). In the post-war years, open manipulations with the obvious facts of World War II took place in Tito's Yugoslavia. In the 1990s the memories repressed during the communist years were set free and publicly debated. After the fall of the one-party system the memory of World War II was devalued. The memory of the Russian-Serbian military fraternity forged during the World War II began to revive in Serbia due to the foreign policy changes in 2008. In October 2008 the President of Russia paid a visit to Serbia which began the process of (re) construction of World War II in Serbian historical memory. According to the public opinion surveys, a positive attitude towards Russia and Russians in Serbia strengthens the memories on general resistance to Nazism with memories of fratricide during the civil conflict events of 1941-1945 still dominating in Serbian society.